Effect of carvacrol and thymol on Salmonella spp. biofilms on polypropylene. (25th August 2015) - Amaral, Viviane C. S.; Santos, Patrícia R.; da Silva, Alex Fiori; dos Santos, Adriele Rodrigues; Machinski, Miguel; Mikcha, Jane M. Graton
Summary: The present study evaluated the effects of carvacrol and thymol against Salmonella spp. biofilm on polypropylene. The efficacy of the compounds was assessed by quantifying Salmonella spp. cells during and after biofilm formation on polypropylene and performing scanning electron microscopy. During biofilm formation, carvacrol and thymol, at subinhibitory concentrations, reduced bacterial counts about 1–2 log, while established Salmonella spp. biofilms were reduced about 1–5 log by carvacrol and thymol, at MIC or 2× MIC. The greatest reduction in carvacrol‐treated biofilms, about 5 log, was observed with 156 and 312 μg mL −1 (MIC and 2× MIC) in established Salmonella Typhimurium ATCC 14028 biofilms. Thymol showed the greatest reduction, about 4 log, at 624 μg mL −1 (2× MIC) against mature Salmonella Enteritidis biofilm. Carvacrol and thymol reduced the number of Salmonella spp. cells on polypropylene, suggesting their potential for the control of Salmonella spp. biofilms. Abstract : Graphical abstract represents the effects of carvacrol and thymol against Salmonella spp. biofilm on polypropylene. Carvacrol and thymol reduced the number of bacterial cells on polypropylene, suggesting their potential for the control of Salmonella spp. biofilms.